Uniform experimental design optimization of liquid fermentation Baijiu mixed fermentation - Peng, Wei; Peng, Jinmei; Lan, Luling; Li, Huazhi; Ning, Xinqiang (International Journal of Agriculture and Food Sciences Research, 2024)
In this study, corn alcohol fermentation mash was used as raw material, and different microorganisms were added to improve the flavor of liquid fermentation Baijiu. The optimum fermentation conditions of liquid fermentation Baijiu were optimized by uniform experimental design. The optimum fermentation conditions were as follows: Saccharomyces cerevisiae: non-Saccharomyces cerevisiae=3.8:1, yeast inoculation amount was 0.65 g/g, Lactobacillus inoculation amount was 1%, yeast inoculation time was 26.5 h, Lactobacillus inoculation time was 0.5 h, the total acid content was 1.943 g/L, the estimated total acid yield was 2.036 g/L, and the relative deviation was 0.077%. Compared with the three control groups, the total acid yield increased by 27.39%, 12.36% and 19.05% respectively.